(untitled) (American Journal of Islam and Society, 2014)
M. Hakan Yavuz was one of the early contributors to the literature on the Gülen movement, co-editing a major volume on the subject with John Esposito in 2003 (Hakan Yavuz and John Esposito, Turkish Islam and the Secular State: The Gülen Movement [Syracuse University Press: 2003]). In the intervening decade the movement has grown considerably in size and influence both within Turkey and beyond, and has emerged as a major source of interest and apparently perennial controversy. Towards an Islamic Enlightenment is therefore a timely if ambitious book, for it sets out to provide a comprehensive account of the movement. The author opens with an analysis of Fethullah Gülen’s theological teachings and then explores the movement’s structure and organization, as well as its emergence and development in the context of Turkish social, religious, and political history. No other scholar has attempted such a holistic analysis, for others tend to focus on just one of its many areas of influence, namely, education (Bekim Agai, Zwischen Netzwerk und Diskurs - Das Bildungsnetzwerk um Fethullah Gülen (geb. 1938): Die flexible Umsetzung modernen islamischen Gedankengutes [EB-Verlag, 2004]), politics (Berna Turam, Between Islam and the State: The Politics of Engagement [Stanford University Press: 2007]), and economic enterprise (Joshua D. Hendrick, Gülen: The Ambiguous Politics of Market Islam in Turkey and the World [New York Press: 2013]). Yavuz lays out his thesis of “Islamic Enlightenment” in the introduction by drawing a paradigmatic distinction between the Muslim intellectual tradition’s literalist/fundamentalists and modernist/reformists. He acknowledges the impact of Enlightenment ideas on the major thinkers in the latter category, but notes that those ideas have historically remained the preserve of the Muslim elite and never “penetrated the masses” (p. 6). According to Yavuz, the ...